Urban housing affordability, economic disadvantage and racial disparities in gun violence: A neighbourhood analysis in four US cities - Stansfield, Richard (The British journal of criminology, 2023)
This study seeks to examine how urban affordability, and related issues of eviction and joblessness, are associated with gun violence in the United States. After discussing the theoretical importance of studying housing affordability, we provide a preliminary examination of how urban affordability moderates the relationship between other markers of economic disadvantage and gun violence. This study further considers whether these different indicators of disadvantage are associated with gun violence differently by majority Black and majority White neighbourhoods. This study rests on neighbourhood-level data from 4 large US cities. Through a series of fixed-effects models, our results reveal that changes in affordability are significantly associated with rising gun violence in general, particularly in majority Black neighbourhoods. Furthermore, joblessness and eviction are less influential in shaping gun violence in more affordable neighbourhoods, but more consequential in communities facing higher rent burdens. The study reiterates several recommendations about reducing unaffordability in urban communities, as well as recommending several avenues for future research on urban violence.